The letters of Arturo Toscanini - Toscanini, Arturo 1867-1957; Sachs, Harvey 1946- (New York Knopf, 2002)
Toscanini (1867–1957) was one of the most celebrated and influential symphonic and operatic conductors in history. With his amazing ear and photographic memory, his sense of moral imperative and iron will, he raised the standards of orchestras and opera companies to previously undreamed-of heights. He conducted the world premieres of Leoncavallo’s Pagliacci and Puccini’s La bohème, The Girl of the Golden West, and Turandot. His sixty-eight-year conducting career began before Verdi had completed Otello and lasted into the era of televised concerts and stereophonic sound. He headed such ensembles as La Scala, the Metropolitan Opera, the New York Philharmonic, and the NBC Symphony Orchestra. Yet he never wrote a memoir, or even essays for publication, or granted interviews. Now we are brought closer to him than we have ever been—in seven hundred letters, well over ninety percent of them previously unpublished in any language. The letters are vivid and impassioned. They reveal a complicated man, often angry and unhappy, who was also capable of great generosity of spirit, self-irony, and humor. They show the depth of his musical knowledge and insight, and shed much light on the musical life of his time in Europe, in New York, and throughout the world. There is fascinating correspondence with his wife and children, and with colleagues and friends, and he writes, as well, about his affairs and erotic adventures. He expresses particular vehemence when talking about his active opposition to fascism and Nazism.
Includes bibliographical references and index
Keywords: Toscanini, Arturo -- 1867-1957; 20th Century (1901-2000); Conductor; Correspondence; Music history; Fascism; Europe; Italy